2021
DOI: 10.2166/nh.2021.008
|View full text |Cite
|
Sign up to set email alerts
|

Flood routing via a copula-based approach

Abstract: Floods are among the most common natural disasters that if not controlled may cause severe damage and high costs. Flood control and management can be done using structural measures that should be designed based on the flood design studies. The simulation of outflow hydrograph using inflow hydrograph can provide useful information. In this study, a copula-based approach was applied to simulate the outflow hydrograph of various floods, including the Wilson River flood, the River Wye flood and the Karun River flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Where f is the joint density distribution; f x i i ( ) is the marginal density distribution of the random variable x i , where i d = 1 2 , ,  ; and c is the density of the Copula function. More details about the Copula can be found in Khozeymehnezhad and Nazeri-Tahroudi (2020) and Nazeri-Tahroudi et al (2022). Our article mainly introduced and used the six typical Copula functions that were widely applied (Supplementary Table S1).…”
Section: Vine Copula Functionmentioning
confidence: 99%
“…Where f is the joint density distribution; f x i i ( ) is the marginal density distribution of the random variable x i , where i d = 1 2 , ,  ; and c is the density of the Copula function. More details about the Copula can be found in Khozeymehnezhad and Nazeri-Tahroudi (2020) and Nazeri-Tahroudi et al (2022). Our article mainly introduced and used the six typical Copula functions that were widely applied (Supplementary Table S1).…”
Section: Vine Copula Functionmentioning
confidence: 99%
“…Based on this aspect, Tahroudi et al . (2021) and Khashei‐Siuki et al . (2021) used vine copula to simulate flood hydrograph and potential evapotranspiration model, respectively, in their studies.…”
Section: Introductionmentioning
confidence: 99%
“…The complete freedom to select bivariate copula in each step of hierarchical structure provides elevated flexibility in vine copula based multivariate dependence modelling than traditional copulas (Ni et al, 2020). Based on this aspect, Tahroudi et al (2021) and Khashei-Siuki et al (2021) used vine copula to simulate flood hydrograph and potential evapotranspiration model, respectively, in their studies. They found that the efficiency of vine copula in dependence analysis was good and accurate.…”
Section: Introductionmentioning
confidence: 99%